Winter is coming: deciphering the longitudinal associations between everyday emotion regulation and depressive symptoms across the seasons - Strakosch, Ana-Maria; Schulze, Katrin; Miano, Annemarie; Prüßner, Luise; Barnow, Sven (Current psychology, 2024)
The dynamic interplay between emotion regulation and seasonal fluctuations in depressive symptoms remains poorly understood. Our study therefore investigated the prospective relationship between everyday emotion regulation and depressive symptoms across summer, autumn, early winter, and late winter. At each season, participants (N = 194) were asked to report their use of emotion regulation strategies (rumination, suppression, reappraisal, acceptance) using ecological momentary assessment, and to fill in online questionnaires. We observed an increase in depressive symptoms and rumination from summer to early winter, while acceptance decreased over the seasons. Participants with an overall higher use of acceptance demonstrated lower depressive symptoms. In contrast, participants showing a greater engagement in suppression, rumination, and reappraisal exhibited higher depressive symptoms, with the latter two strategies emerging as temporal precursors of symptom severity. These findings highlight the clinical importance of emotion regulation in explaining seasonal fluctuations in depressive symptoms.